VITAMIN B12 AND OBESITY: REVIEW - Maryam Kadhim Al-Shemery; Rusul Ali Al-Masaoodi (European Science Publishing, 2024)
The primary reason behind the increasing increase in overweight is increased consumption of calories, while several other variables such as inheritance as well as exercise certainly contribute. Numerous studies have connected the amount of vitamin B12 to overweight. The present investigation aimed at determining that predict vitamin B12 pathology in persons who are obese at the beginning of their lives. They additionally provide recommendations about the potential uses of B12 in therapy contexts, specifically in the area of obesity prediction. B12 (vitamin may be used to forecast the possibility of disease and to spot indicators associated with anxiety and overweight. Furthermore, a number of studies investigated into a connection between MS and the vitamin B complex, including the presence of folic acid and vitamin B12.
Keywords: Obesity, B12, metabolic syndrome, cardiovascular disease, insulin resistance.